Evaluasi Kualitas Sistem Informasi Perencanaan dan Penganggaran Badan Perencanaan, Penelitian, Pengembangan Kota Malang dengan Technology Acceptance Model (TAM) Termodifikasi - Asa Arifudin; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
This research was conducted to describe the level of acceptance of the system by using variables adopted from the modified Technology Acceptance Model (TAM) research model, namely perceived usefulness, perceived ease of use, user characteristics, system quality and top management and IT support using descriptive statistics analysis. Data were collected using questionnaires consisting of 29 statements made using 5 point likert scale to 100 respondent users of the Planning and Budgeting Information System which were distributed to all Malang City Government agencies. A total of 94 questionnaires were obtained and the results showed that the variables top management and IT support and perceived usefulness included in very high categories and the variables system quality and perceived ease of use included in high categories. Recommendations given to improve the level of acceptance are conducting technical evaluations by testing the system, conducting intensive training to the users towards the system usage phase to improve understanding of the system and providing a call center to handle customer services including aspirations, criticisms and suggestions from customers for evaluating the system.